Dialogues on mainstreaming gender dimensions into water issues:: interview with Alice M. Bouman-Dentener - Saito, Carlos Hiroo; Nogueira, Daniela (Sustainability in Debate, 2017)
Interview script with Drs. Alice M. Bouman-Dentener, Vice-President of the Water Research and Training Centre of Myanmar (WRTC), chairs the Members Council of the European Water Stewardship (EWS) and is member of the Advisory Board of Gender Concerns International (GCI)